Antagonistic Activity of Lactobacillus Isolates against Salmonella typhi In Vitro. (29th September 2013) - Abdel-Daim, Amira; Hassouna, Nadia; Hafez, Mohamed; Ashor, Mohamed Seif Aldeen; Aboulwafa, Mohammad M.
Abstract : Background . Enteric fever is a global health problem, and rapidly developing resistance to various drugs makes the situation more alarming. The potential use of Lactobacillus to control typhoid fever represents a promising approach, as it may exert protective actions through various mechanisms. Methods . In this study, the probiotic potential and antagonistic activities of 32 Lactobacillus isolates against Salmonella typhi were evaluated. The antimicrobial activity of cell free supernatants of Lactobacillus isolates, interference of Lactobacillus isolates with the Salmonella adherence and invasion, cytoprotective effect of Lactobacillus isolates, and possibility of concurrent use of tested Lactobacillus isolates and antibiotics were evaluated by testing their susceptibilities to antimicrobial agents, and their oxygen tolerance was also examined. Results . The results revealed that twelve Lactobacillus isolates could protect against Salmonella typhi infection through interference with both its growth and its virulence properties, such as adherence, invasion, and cytotoxicity. These Lactobacillus isolates exhibited MIC values for ciprofloxacin higher than those of Salmonella typhi and oxygen tolerance and were identified as Lactobacillus plantarum . Conclusion . The tested Lactobacillus plantarum isolates can be introduced as potential novel candidates that have to be subjected for in vivo and application studies for treatment and control of typhoid fever.